The complete mitochondrial genome sequence of Acentrogobius caninus (Gobiiformes: Gobiidae) - Shi, Wei (Mitochondrial DNA B Resour, 2018)
At present, only several species of genus Acentrogobius were described and information of mitochondrial DNA were also just focused on two species. Here, the complete mitochondrial genome of Acentrogobius caninus was completely sequenced by high throughput sequencing method. The complete mitochondrial genome was 16,614 bp in length, consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, 1 large non-coding control region, and 1 light-strand replication origin. Overall base composition values for the mitochondrial genome were 28.24, 29.20, 16.77, and 25.79% for A, C, G, and T, respectively. The gene arrangement is identical to those in typical fishes. Phylogenetic tree based on 13 protein-coding genes shows that three species of genus Acentrogobiu did not cluster into one clade.